Liquidity and credit risks in the UK's financial crisis: How "quantitative easing" changed the relationship - Woon K. Wong; Iris Biefang-Frisancho Mariscal; Wanru Yao; Peter G. A. Howells (Cardiff University, Cardiff Business School, 2016)
This paper investigates the relationship between credit and liquidity risk components in the UK interbank spread during the recent financial crisis and sheds light on the transmission mechanism of the quantitative easing (QE) carried out by the Bank of England on short term interest rates. Specifically, we find that prior to the Bank's intervention counterparty risk was a major factor in the widening of the spread and also caused a rise in liquidity risk. However, this relationship was reversed during the period when QE was implemented. Using the accumulated value of asset purchases as a proxy for the central bank's liquidity provisions, we provide evidence that the QE operations were successful in reducing liquidity premia and ultimately, and indirectly, credit risk. We also find evidence that suggests liquidity schemes provided by other central banks and international market sentiment contributed to the reduction of interbank spread.
Keywords: 330; interbank spreads; liquidity premia; credit risk; quantitative easing; financial crisis